Association of Tumor Necrosis Factor α Inhibitor Use with Diagnostic Features and Mortality of Tuberculosis in the United States, 2010–2017. (22nd December 2021) - Katrak, Shereen S; Li, Rongxia; Reynolds, Sue; Marks, Suzanne M; Probst, Jessica R; Chorba, Terence; Winthrop, Kevin; Castro, Kenneth G; Goswami, Neela D
Abstract: Background: An elevated risk of tuberculosis (TB) disease in persons who have received tumor necrosis factor alpha inhibitor medications (TNF-α inhibitors) has been reported for nearly two decades, but clinical diagnostic features and outcomes of TB in this population remain poorly described. Methods: We analyzed national surveillance data for TB cases among persons aged 15 years and older reported in the United States during 2010–2017 and associated mortality data reported through 2019 to describe the clinical characteristics of those receiving TNF-α inhibitors. Results: Of 70 129 TB cases analyzed, 504 (0.7%) of the patients had TNF-α inhibitor use reported at TB diagnosis. Patients with TNF-α inhibitor use at TB diagnosis were more likely than TB patients not receiving TNF-α inhibitors to have TB diagnosed in extrapulmonary sites in conjunction with pulmonary sites (28.8% vs 10.0%, P < .001). Patients receiving TNF-α inhibitors were less likely to have acid-fast bacilli noted on sputum smear microscopy (25.6% vs 39.1%, P = .04), and more likely to have drug-resistant disease (13.5% vs 10.0%, P < .001). TB-attributed deaths did not significantly differ between patients receiving and not receiving TNF-α inhibitors (adjusted odds ratio, 1.46 [95% confidence interval, .95–2.26]). Conclusions: Clinicians evaluating TNF-α inhibitor–treated patients should have a high index of suspicion for TB and be aware that extrapulmonary or sputum smear–negative TB disease is more common in these patients. No significantly diminished survival of TB patients treated with TNF-α inhibitor therapy before TB diagnosis was noted.